Root allometry of two subtropical plant communities of northeastern Mexico - De los Ríos Carrasco, Eduardo; Návar Cháidez, José de Jesús (Universidad Autónoma de Yucatán, 2010)
This research work aimed at the study of the root allometry in subtropical Tamaulipan thornscrub and pine forest communities of Nuevo Leon, Mexico. By excavating each individual root of each of 20 trees per plant community, we developed root allometric equations for biomass, volume, total length and diameter. Covariance analysis, ancova, was employed to determine the statistical difference of these parameters between plant communities. Results indicate that pine plant trees have larger root volumes, longer root systems and higher root basic densities than trees of Tamaulipan thornscrub forests. This piece of information is key to estimate root biomass, volume, total length and diameter of roots of trees of these plant communities at the stand scale; important environmental information.Key words: Power equations, ancova, root biomass, volume, length and diameter.